-2(b+5)=-b

Simple and best practice solution for -2(b+5)=-b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(b+5)=-b equation:


Simplifying
-2(b + 5) = -1b

Reorder the terms:
-2(5 + b) = -1b
(5 * -2 + b * -2) = -1b
(-10 + -2b) = -1b

Solving
-10 + -2b = -1b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add 'b' to each side of the equation.
-10 + -2b + b = -1b + b

Combine like terms: -2b + b = -1b
-10 + -1b = -1b + b

Combine like terms: -1b + b = 0
-10 + -1b = 0

Add '10' to each side of the equation.
-10 + 10 + -1b = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -1b = 0 + 10
-1b = 0 + 10

Combine like terms: 0 + 10 = 10
-1b = 10

Divide each side by '-1'.
b = -10

Simplifying
b = -10

See similar equations:

| 6t+8-6t+3= | | (m-4)(m+6)=0 | | m-5=-6+m | | 6(x+2)=2(2x+4) | | 3x-16(4-2x)=6 | | 24a+-22=-4(1+6a) | | p=2(89)+2(117) | | -2x-3=x+3+3x | | (x+3)+2(x-7)=3x-11 | | a(10)-8=-24 | | 2y^2+4y-198=0 | | 18-43=4(x-2)-5 | | 9x-(4x-15)=50 | | 2(4r+6)=12r+18 | | 8-9=-12 | | 3z+1=4z-8+28 | | 12(x-9)=-5-7 | | 8=(x+0.5)(x+1) | | x*x+10x=1575 | | 3x-64-32x=6 | | x+50+2x+20=90 | | -6k+7k-9k+8k= | | x+50+2x+20=180 | | 2370=320*144*15*x/35000 | | 49a^4b-14a^3b+21ab=0 | | -2(-3x+8)+5=-21 | | 4x-70=12x+2 | | 6(3a+1)-30=3(20a-4) | | 16=(x+0.5)(x+0.5) | | 2h-35=12h-10h+15 | | 2x+7x+10=11x | | x+2+x+4+x^2-3x+3x-2=39 |

Equations solver categories